IMPACT OF COVID-19 ON SHARIA BANK PROFITS: A CASE STUDY AT BANK MUAMALAT - Khoerulloh, Abd Kholik; Puneri, Atharyanshah (Universitas Airlangga, 2023)
The entry of the COVID-19 into Indonesia caused the paralysis of the Islamic banking system, including Bank Muamalat. This study aims to determine how the impact of covid-19 entry into Indonesia on Bank Muamalat's operating profit. This study uses a descriptive method with a comparative approach with financial statement data, namely the period before entering covid-19 (2017 to 2019) and the period after entering covid-19 (2020 to 2022). The results of this study indicate that the value of Asymp. Sig. (2-tailed) value is 0.006 <0.05. This means that there is a difference in the operating profit of Bank Muamalat before and after the entry of Covid-19 into Indonesia. These results indicate that the COVID-19 pandemic has a real impact on the financial performance of Bank Muamalat, especially in terms of operating profit. This shows the importance of analysing how changes in the global situation, such as a pandemic, can affect financial institutions, including Islamic banking. In this context, Bank Muamalat may have to take certain actions or strategies to overcome the challenges arising from the pandemic.